CHALLENGES AND STRATEGIES IN CROSS-CULTURAL COMMUNICATION: A CASE STUDY OF RESTOURANT WORKERS AND FOREIGN TOURIST AT BURGERKING - Izzah, Arina Nur (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2026)
This study explores the challenges and strategies in cross-cultural communication experienced by restaurant workers at Burger King Waru Sidoarjo when interacting with foreign tourists. As global tourism increases, effective communication becomes essential in service industries. Using a qualitative case study approach, data were collected through questionnaires and observations involving 15 restaurant employees. The results show that workers often face difficulties such as understanding foreign accents, limited English vocabulary, nervousness, and cultural misunderstandings. Despite these challenges, they applied practical communication strategies including using simple English, gestures, code-switching, repetition, and clarification techniques. These strategies helped reduce miscommunication and improved service quality. The findings are analyzed using key theories such as Communicative Competence Theory, High and Low Context Cultures, Politeness Theory, and Communication Accommodation Theory. The study concludes that although workers have not received formal training, they demonstrate adaptive skills in real-life interactions. It is recommended that future training programs focus on improving both language and intercultural communication skills to better serve international customers.